2020
DOI: 10.5398/tasj.2020.43.4.291
|View full text |Cite
|
Sign up to set email alerts
|

Association between GH (g.1456_1457insT), GHRH (g.4474 C>A), and Pit-1 (g.244G>A) Polymorphisms and Lactation Traits in Holstein Friesian Cattle

Abstract: Lactation traits are controlled by many genes, among others, potentially by growth genes. This research was conducted to study genetic polymorphisms of GH, GHRH, and Pit-1 genes and associations of GH (g.1456_1457 InsT), GHRH (g.4474 C>A), and Pit-1 (g.244 G>A) genotypes with milk yield and quality in Holstein Friesian (HF) cattle. Genotyping was conducted for HF dairy cows raised by small farmers from North Lembang (SF-NL) (98 heads) and South Lembang (SF-SL) (95 heads), and also from Cikole Dairy Cattle Stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…PIT-1 is a member of the POU domain taking an important role in cell differentiation and proliferation [12]. A number of previous studies have shown a fairly high genetic polymorphism of the GH, GHRH and PIT-1 genes in cattle and buffalo [9,13,14,15]. Information on genetic polymorphisms of growth family genes in local swamp buffalo is still limited.…”
Section: Introductionmentioning
confidence: 99%
“…PIT-1 is a member of the POU domain taking an important role in cell differentiation and proliferation [12]. A number of previous studies have shown a fairly high genetic polymorphism of the GH, GHRH and PIT-1 genes in cattle and buffalo [9,13,14,15]. Information on genetic polymorphisms of growth family genes in local swamp buffalo is still limited.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the SNP c.73T>C polymorphism was successfully identified using PCR-RFLP with AciI restriction enzyme (5-C|CGC-3). PCR-RFLP was widely used to identify the gene polymorphism associated with economic traits of animals, such as body compositions, lactation, reproduction, immune system, fatty acids composition, carcass, and meat quality [30][31][32][33]. This study revealed three genotypes of TT, TC, and CC.…”
Section: Discussionmentioning
confidence: 99%